Scaling Laws in Supramolecular Polymer Networks - Xu, Donghua (2011)
The linear rheological properties of networks formed by adding bis-Pd(II) cross-linkers to poly(4-vinylpyridine) (PVP) solution are examined, and the scaling law relationships between the zero shear viscosity (η(0)) of the networks versus the concentration of PVP solution (C(PVP)), the concentration of cross-linkers (C(X)), and the number density of elastically active chains (v(phantom)) are experimentally determined. The scaling law relationships are compared to the theoretical expectations of the Sticky Rouse and Sticky Reptation models (Macromolecules 2001, 34, 1058-1068), and both qualitative and quantitative differences are observed.